STUDI KASUS : PENERAPAN TERAPI RELAKSASI OTOT PROGRESIF UNTUK MENURUNKAN NYERI KEPALA PADA PENDERITA HIPERTENSI KELURAHAN METESEH KECAMATAN TEMBALANG - Dewi, Puspita; Hani, Umi (NHM PRESS, 2023)
Middle age family or middle age is the middle age of a person when he is between 45 and 59 years old. Health problems that usually occur in middle age are chronic diseases. Hypertension is the most common condition encountered in society. The characteristics of middle adulthood are a general decrease in physical fitness and a decrease in health. The population is susceptible to disease in adulthood is influenced by many things, including genetic factors, biological factors (age and weight gain), physical factors, lifestyle. The management of non-pharmacological nursing care is intended to assist hypertensive patients in maintaining blood pressure at a normal level so as to improve the condition of their illness, one of which is by using progressive muscle relaxation. . The case study report was conducted in April 2023 for 3 days. The implementation provided is in accordance with IDHS, SIKI and SLKI. The results of the case study were obtained after 3 days of nursing actions. Evaluation of the diagnosis of pain decreased the headache scale after nursing intervention was carried out with progressive muscle relaxation therapy. Families and clients already understand and recognize the problem of hypertension. So it was concluded that the problem of ineffective health care for clients has been resolved. It is expected that families can always pay attention to the health of their families who have hypertension and can deal with headaches independently by using progressive muscle relaxation.